1996
DOI: 10.1016/s0304-3940(96)12438-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of FK506, an immunosuppressant, on transient global ischemia in gerbil

Abstract: Delayed neuronal death (DND) in CA1 region after transient global ischemia is a well-known phenomenon, but its mechanism has not been clarified. In order to examine the involvement of nitric oxide (NO) in DND, 7-nitro indazole (7NI), a selective neuronal NO synthase (nNOS) inhibitor, and FK506, an immunosuppressant which also inhibits nNOS, were administered intraperitoneally during and after transient global ischemia in gerbil. FK506 moderately ameliorated DND in a dose-dependent manner. However, 7NI showed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…In the gerbil, a single injection of FK506 (1.0 mg/ kg) ip did not prevent ischemia-induced CA1 cell death. In contrast, the same dose given daily for four days provided neuroprotection, without hypothermia during the 24 h following FK506 administration (8,9). In rats, FK506 prevented ischemia-induced brain damage without reducing core temperature when given daily for 4 (10) or 14 days (19).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In the gerbil, a single injection of FK506 (1.0 mg/ kg) ip did not prevent ischemia-induced CA1 cell death. In contrast, the same dose given daily for four days provided neuroprotection, without hypothermia during the 24 h following FK506 administration (8,9). In rats, FK506 prevented ischemia-induced brain damage without reducing core temperature when given daily for 4 (10) or 14 days (19).…”
Section: Resultsmentioning
confidence: 95%
“…The importance of immunophilins in the development of neuroprotectors emerged from observations that compound FK506 provides neuroprotection against glutamate-induced neurotoxicity in vitro (5), and in the rodent model of focal cerebral ischemia employing intracerebrally applied endothelin-1 (6). These findings have been extended to models of transient global forebrain ischemia (7)(8)(9)(10). FK506 is a fungal-derived macrolide exhibiting a potent immunosuppressant action, and has been recently introduced in clinical practice to prevent allograft rejection.…”
Section: Introductionmentioning
confidence: 94%
“…Inflammation plays a role in propagating cerebral ischemic injury and, consequently, immunosuppressive agents improve outcome in experimental models of stroke (1)(2)(3)(4). Most available immunosuppressive agents, however, have systemic side effects that would limit therapeutic use in stroke.…”
mentioning
confidence: 99%
“…It is observed that tacrolimus (FK506), a fungal-derived macrolide, has potent immunosuppressant effects which can provide neuro-protection against glutamate-induced neurotoxicity in animal models of focal (8)(9)(10) or transient, global forebrain ischemia (11,12). Many studies have shown that FK506 reduces hippocampal pyramidal cell death after TGCI in the gerbil (11,12) and rat two-vessel occlusion (2-VO) models (13). This effect is due to the interaction of FK506 with the immunophilin FKBP12 (FK506-binding protein) by inhibiting phosphatase calcineurin (14).…”
Section: Introductionmentioning
confidence: 99%